[tex]\frac{2x^2+4x+2}{x^2-x-2} =1[/tex][tex]\frac{2(x+1)^2}{x*(x+1)*(x-2)} =1[/tex][tex]\frac{2(x+1)^2}{(x+1)(x-2)}=1[/tex][tex]\frac{2(x+1)}{x-2}=1[/tex][tex]\frac{2x+2}{x-2}=1[/tex][tex]2x+2=x-2[/tex][tex]2x-x=-2-2[/tex][tex]x=-4[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
[tex]\frac{2x^2+4x+2}{x^2-x-2} =1[/tex]
[tex]\frac{2(x+1)^2}{x*(x+1)*(x-2)} =1[/tex]
[tex]\frac{2(x+1)^2}{(x+1)(x-2)}=1[/tex]
[tex]\frac{2(x+1)}{x-2}=1[/tex]
[tex]\frac{2x+2}{x-2}=1[/tex]
[tex]2x+2=x-2[/tex]
[tex]2x-x=-2-2[/tex]
[tex]x=-4[/tex]